(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the characteristics of recovery of patients undergoing laparoscopic lobectomy at K hospital according to the Aldreter scale. Subjects and method: Prospective study of 152 patients after laparoscopic lobectomy at Tan Trieu K Hospital. Results: Perception was the earliest scoring criterion, Aldrete score ≥ 9 was mainly less than 3 hours (71.7%).he pain care work of nurses was 93.5% effective. Conclusions: According to the Aldreter scale, perception is the criterion with the earliest time to achieve, the majority to achieve Aldreter score ≥ 9 mainly under 3 hours (71.7%).